A COMPARATIVE STUDY OF KAPAL BHATI AND MEDOHARA ARKA IN THE MANAGEMENT OF STHAULYA (OBESITY) - Garg, *Gunjan; Mangal, Gopesh; Chundawat, N.S. (International Journal of Ayurveda and Pharma Research, 2016)
Obesity is a blessing of the Modern age of Machines and Materialism. The impact of modern civilization has absolutely changed our life styles. Most of the peoples are forced to live a sedentary life. Obesity is a type of disease, which invites many major & minor manifestations. Ayurveda has described one of such disorder as Sthaulya. The parallel in western medicine to this order is “Obesity. It is clinically prove that both Yoga and Ayurveda are mutually supportive and offer many ways to prevent and heal various disorders as well as cleanse and rejuvenate the body. Kapal Bhati is reliable to control the Sthaulya. Medohara Arka is known to exert several beneficial physiological effects including the anti-obesitic influence.Study Design: 90 patients, randomly divided into three groups with 30 patients in each group. In Group A, Kapal bhati was administered twice a day for 15 minutes in morning and evening on empty stomach for 45 days. In Group B, Medohara arka was administered in 30 ml dose with Madhu anupana twice a day for 45 days and in Group C, both Kapal Bhati and Medohara arka was administered as mentioned above.Results & Conclusion: Marked Improvement was not observed in any of the groups. Moderate Improvement was observed in 6.66 % patients in Group A and 3.33% in Group C. Mild Improvement was observed in 80% patients in Group C and 60% patients in Group A & 53.33% in Group B. No improvement was observed as 36.66% in Group B, 33.33% in Group A and 16.66% in Group C. Thus, it can be concluded that the Kapal Bhati along with Medohara Arka is effective in the management of Sthaulya as it is safe, cost effective and free from any side effects.